Legal Agreements and the Governance of Research Commons: Lessons from Materials Sharing in Mouse Genomics - Mishra, Amrita (Mary Ann Liebert, Inc., 2014)
Omics research infrastructure such as databases and bio-repositories requires effective governance to support pre-competitive research. Governance includes the use of legal agreements, such as Material Transfer Agreements (MTAs). We analyze the use of such agreements in the mouse research commons, including by two large-scale resource development projects: the International Knockout Mouse Consortium (IKMC) and International Mouse Phenotyping Consortium (IMPC). We combine an analysis of legal agreements and semi-structured interviews with 87 members of the mouse model research community to examine legal agreements in four contexts: (1) between researchers; (2) deposit into repositories; (3) distribution by repositories; and (4) exchanges between repositories, especially those that are consortium members of the IKMC and IMPC. We conclude that legal agreements for the deposit and distribution of research reagents should be kept as simple and standard as possible, especially when minimal enforcement capacity and resources exist. Simple and standardized legal agreements reduce transactional bottlenecks and facilitate the creation of a vibrant and sustainable research commons, supported by repositories and databases.